Pengembangan Karir, Kepuasan dan Disiplin Kerja terhadap Kinerja Karyawan PT Pos Indonesia (Persero) Cabang Surakarta - Arum Tantya; Ratna Damayanti (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2023)
This study aims to determine and explain the effect of simultaneous or partial career development, job satisfaction and discipline on the performance of employees of PT Pos Indonesia (Persero) Surakarta Branch. The research method uses a quantitative approach, in the form of a questionnaire. The sample in this study amounted to 70 respondents who were divided into employees of PT Pos Indonesia (Persero) Surakarta Branch. The data used in this study is primary data in the form of the results of questionnaires filled out by respondents. The analytical method used is quantitative analysis, multiple linear regression, F test, t test and coefficient of determination with SPSS version 21 program.The results of this study indicate that career development has a positive and significant effect on the performance of employees of PT Pos Indonesia (Persero) Surakarta Branch, satisfaction has a positive and significant effect on the performance of employees of PT Pos Indonesia (Persero) Surakarta Branch, work discipline has a positive and significant effect on employee performance at PT. Pos Indonesia (Persero) Surakarta Branch. Keywords : Employee Performance, Career Development, Satisfaction, Work Discipline